THE EFFECT OF SHARIA FINANCING AND FINANCING-TO-DEPOSIT-RATIO TOWARD PROFITABILITY AND CREDIT QUALITY LEVEL OF ISLAMIC BANKING IN INDONESIA - Nugraha, Dicky
As a country with the highest Muslim population in the world, Islamic banking system becomes an important element in Indonesia. the role of banks for both the macroeconomic and microeconomic activities cannot be denied. The banking system has a significant role in the economy as a whole. The development of Islamic banking has produced various achievements, from the increasing number of products and services to the development of infrastructure that supports sharia finance. However, the growth of Islamic finance has not been able to keep up with conventional financial growth. It can be proven by some financial indicators such as profitability and credit quality level of Islamic banking compared to the conventional banking. Although the Non Performing Financing ratio of Islamic banks in Indonesia is decreasing over the year, the level of NPF decreases is not too significant. Moreover, the NPF level of Islamic banks is still higher that the NPF level of conventional banks. Not only the higher level of NPF compared to the conventional banks, Islamic banks in Indonesia have quiet low profitability level. The profitability level can be seen from its return on assets (ROA). Islamic bank return on assets (ROA) is lower than small conventional banks with capital of less than IDR 1 trillion. The reason why the profitability level of Islamic bank is still lower than the conventional ones is that Islamic bank bears the higher cost of funds followed by the increases of operational banks. It makes the customers feel that conventional banking is more favorable than Islamic banking service. This research is aimed to examine the effect of Sharia financing provided by Islamic banks in Indonesia and its proportion against the total deposit (FDR) towards the profitability level represented by ratio of ROA and the credit quality level represented by ratio of NPF net. This study used quantitative approach by obtaining secondary data from six Islamic banks’ quarterly financial reports from 2015 Q2 until 2019 Q1. The independent variables obtained are Sharia financing which includes Murabaha, Mudaraba, and Musharaka financing, and also a financing-to-deposit ratio (FDR). A multiple linear regression is used as a statistical tool for analyzing the relationships of these independent variables against the ROA and NPF level. A five classical assumptions testing and hypothesis testing are also conducted as a requirement in conducting multiple linear regression analysis for analyzing the data. From this research, it can be found that Murabaha has a positive and significant effect on ROA. Whereas Mudaraba and Musharaka, which are categorized as profit-and-loss-sharing (PLS) financing, have negative and significant relationship towards ROA. FDR does not significantly influence the level of ROA. The second model shows that Murabaha financing and FDR have a negative and significant relationship towards the ratio of NPF-net. Whereas Mudaraba and Musharaka have positive and significant effect on NPF-net ratio. The Therefore, Islamic banking should maintain the efficiency of Murabaha financing distribution, and pay more attention to the PLS financing, which includes Mudaraba and Musharaka financing, in order to increase its ability to generate higher profitability and minimize the amount of non-performing financing, due to maintaining and improving its development against the conventional banking.